From Scroll to Checkout: The Forces Shaping Youth Online Shopping in Malaysia - Norfazlirda Hairani; Mohamad Hazeem Sidik; Man Hong Lu (International Journal of Management, Business, and Social Sciences, 2025)
Online shopping has become an integral part of modern consumer behaviour, underscoring the need for the retail players to understand the factors driving its acceptance among youth. This study investigates on how perceived usefulness, perceived ease of use, and trust influence youths’ behavioural acceptance of online shopping. Data were collected from 384 respondents by using purposive sampling through an online questionnaire and analysed with SPSS, employing descriptive statistics, reliability and validity assessments, and also Pearson’s correlation analysis. The results revealed that these variables have a significant positive relationship with online shopping acceptance, with trust emerging as the strongest predictor. These findings offer updated empirical insights into the behavioral patterns of young Malaysian consumers and emphasize the importance of enhancing platform usability, reliability, and credibility to foster greater engagement in online shopping.